Entrepreneurial Skills for Sheep Fattening Youth & Women’s Groups in Ethiopia - Wamatu, Jane; Ekule, Muluken (International Center for Agricultural Research in the Dry Areas, 2022)
A training report on entrepreneurial skills and collective action in sheep fattening youth and women groups